Short homologies efficiently generate detectable homologous recombination events - Osahor, Andrew N.; Tan, Chau-Yan; Sim, Edmund U. H.; Lee, Choon-Weng; Narayanan, Kulathuramaiyer (Academic Press Inc., 2014)
When recombineering bacterial artificial chromosomes (BACs), it is common practice to design the ends of the donor molecule with 50 bp of homology specifying its insertion site. We demonstrate that desired recombinants can be produced using intermolecular homologies as short as 15 bp. Although the use of shorter donor end regions decreases total recombinants by several fold, the frequency of recombinants with correctly inserted donor molecules was high enough for easy detection by simple polymerase chain reaction (PCR) screening. This observation may have important implications for the design of oligonucleotides for recombineering, including significant cost savings, especially for high-throughput projects that use large quantities of primers.